School Map Requirements for Multi-Agency School Emergency Response - Maher, Lauren; Grace, Rob (Proceedings of the International ISCRAM Conference, 2026)
School emergencies routinely involve EMS, fire, and law enforcement responding under distinct objectives and uncertainties, yet these agencies often rely on the same non-standardized school maps, which vary widely in quality and availability. This paper reports findings from a qualitative interview study (n = 10) examining the spatial decision-making and spatial information needs of EMS, fire, and law enforcement responders during school emergency response. Using a Goal-Directed Task Analysis exercise, participants worked through dispatch scenarios using (1) satellite imagery of a school exterior and (2) the same imagery augmented with an indoor school map. Findings identify spatial information needs shared across agencies that support rapid orientation and spatial inference, as well as agency-specific needs tied to distinct operational goals. Results inform requirements for standardized, minimalist school maps that support wayfinding and flexible inference alongside complementary, agency-specific GIS.